2022
DOI: 10.3390/ijerph19031036
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Dysfunction in COVID-19 Patients Who Do Not Report Olfactory Symptoms: A Pilot Study with Some Suggestions for Dentists

Abstract: Background: Smell and taste dysfunction are frequently reported by SARS-CoV-2 positive patients. The degree of olfactory and gustatory dysfunction varies from a very mild reduction to their complete loss. Several studies have been performed to determine their prevalence in COVID-19 patients, mostly using subjective measurement methods. The literature lacks long-term studies regarding duration and recovery. Methods: We assessed olfactory performance, using the Sniffin’ Sticks olfactory test, in a group of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Likely, the subjective perception of olfactory impairment (i.e., using VAS for smell) may lead to poor or absent correlation with the results of olfactory tests [ 16 , 17 ], so a smell test should always be associated with a PROM for smell in order to better define the presence of dysosmia and its severity [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likely, the subjective perception of olfactory impairment (i.e., using VAS for smell) may lead to poor or absent correlation with the results of olfactory tests [ 16 , 17 ], so a smell test should always be associated with a PROM for smell in order to better define the presence of dysosmia and its severity [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the latter patients might have had OD in addition to other more severe neurological symptoms. Moreover, since the olfactory loss was self-reported and not assessed by any objective test, OD prevalence might have been underestimated, as reported in previous studies [ 9 , 36 ]. Our results, along with a previous study finding no difference in OB volume between COVID-19 patients with and without self-reported olfactory loss [ 37 ], suggest that OB atrophy may be associated with the neurological sequelae of COVID-19, even without leading to (self-perceivable) olfactory loss, supporting the hypothesis of SARS-CoV-2 using the olfactory pathway as a gateway to the brain.…”
Section: Discussionmentioning
confidence: 97%
“…We have previously reported that taste test results remain consistent across different ages for both males and females. Recent reports have highlighted cases demonstrating anomalies in the sense of taste and smell due to the COVID-19 epidemic [7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have reported a decline in the sense of smell and taste as an early symptom of Alzheimer's dementia [6]. Additionally, other researchers have reported that having COVID-19 affects one's sense of smell and taste [7][8][9][10][11][12][13][14][15][16]. This time, we decided to compare the data of the same participants in the health checkup for residents of Yakumo Town, Hokkaido, Japan, which we have been conducting for many years, to examine whether the sense of taste and smell changed before and after the COVID-19 epidemic.…”
Section: Introductionmentioning
confidence: 99%